Percepción social de la Inseguridad ciudadana en el Distrito de El Tambo - Huancayo: 2010 - Quispe Matamorros, Sonya Alicia (2011)
Percepción social de la Inseguridad ciudadana en el Distrito de El Tambo - Huancayo: 2010